Prevalence of diarrheal diseases and associated factors among under five children in Africa: A meta-analysis - Eshetu Abera Worede; Asmamaw Malede; Hailemariam Feleke; Geziew Abere; Eyayaw Addissu Demeke; Jember Azanaw (PLoS ONE, 2025)
Background Diarrheal diseases remain a major health threat for children under five in Africa, causing high rates of morbidity and mortality. The regional and continental pooled prevalence and risk factors for childhood diarrhea in Africa remain unknown. This systematic review and meta-analysis (2013–2023) aims to synthesize existing evidence to estimate the pooled prevalence and identify key risk factors associated with childhood diarrhea. Methods Searches were conducted in databases including PubMed, Scopus, Web of Science, and Google Scholar to identify research published between January 2013 to December 2023. The PRISMA flowchart guideline was used to screen studies. A random-effects model was used to estimate the pooled prevalence. Publication bias was assessed using a funnel plot and Egger’s test, with heterogeneity assessed by I2 statistics. Results From the reviewed research, 66 studies met the inclusion criteria and were included in the analysis. The pooled prevalence of diarrheal diseases was 23.59% (95% CI: 21.77–25.42). Sub-group analysis by region revealed the highest prevalence found in Southern Africa (30.14%,) followed by North Africa (28.16%), Central Africa (25.25%), East Africa (24.92%), and West Africa (15.11%). Poor handwashing practices (AOR = 4.69, 95%CI: 2.44–9.04), unimproved water sources (AOR = 1.68, 95%CI: 1.44 1.95), poor solid waste (AOR = 2.29, 95%CI:(1.64 3.20), liquid waste (AOR = 1.72, 95%CI: 1.71–1.723) management, lack of latrine (AOR = 1.17, 95% CI: 1.13–1.22), were significantly associated with DD among under-five children. Conversely, protected water sources (AOR = 0.38, 95% CI: 0.27–0.53), and ventilated improved pit latrines (AOR = 0.85, 95% CI: 0.77–0.95) were protective. Additional risk factors included age (6−11 months: AOR = 1.72, 95% CI:(1.61 1.84);12–23 months: AOR = 2.92, 95% CI:1.60 5.31), lack of exclusive breastfeeding (AOR = 3.06, 95%CI: 2.12–4.43), having more than two under-five children in a household (AOR = 1.48, 95% CI: 1.28–1.71), larger family size (AOR = 2.34, 95% CI: 1.42–3.85), Maternal or caregiver illiteracy (AOR = 2.43, 95%CI: 1.95 3.03), low socioeconomic status (AOR = 1.44, 95%CI: 1.10 1.88) were also significantly associated with DD. Conclusion The pooled prevalence of diarrheal diseases among under-five children in Africa was high. Age of a child, lack of exclusive breastfeeding, having more than two children in a household, low socioeconomic status, maternal or caregiver illiteracy, poor hand washing practices, unimproved water sources, poor solid and liquid waste management, absence of a latrine were factors significantly associated with childhood diarrhea. On the other hand, having a ventilated improved pit latrine and getting water from protected sources were protective factors. These findings highlight critical areas for targeted interventions to reduce diarrheal disease in vulnerable African populations.